Coffee Ring Effect Free TiO2 Nanotube Array for Quantitative Laser Desorption/Ionization Mass Spectrometry - Kim, Moon-Ju; Park, Jong-Min; Noh, Joo-Yoon; Yun, Tae Gyeong; Kang, Min-Jung; Ku, Nam Su; Lee, Eun Hye; Park, Kwang Hwan; Park, Moo Suk; Lee, Sang-Guk; Pyun, Jae-Chul (AMER CHEMICAL SOC, 2020)
Quantitative analysis using laser desorption/ionization mass spectrometry (LDI-MS) has been limited because of the nonuniform distribution of analytes caused by the "coffee ring effect". In this study, a TiO2 nanotube array with hydrophilic dot patterns surrounded by hydrophobic areas (HB/HL-patterned TiO2 NTA) is presented to distribute analytes uniformly as well as to concentrate them within a sample spot. The HB/HL-patterned TiO2 NTA is fabricated by (1) electrochemical anodization, (2) silane functionalization, and (3) hydrophilic patterning with a photomask under ultraviolet radiation. Suppression of the coffee ring effect on this wettability-controlled TiO2 NTA is experimentally elucidated in terms of a capillary penetration of analyte solution into the selectively permeable TiO2 NTA. The morphology of a dried fluorescein on the HB/HL-patterned TiO2 NTA demonstrates homogeneous fluorescein deposition without lateral spreading. The feasibility of HB/HL-patterned TiO2 NTA for quantitative LDI-MS is demonstrated using two types of sepsis biomarkers, lysophosphatidylcholine 16:0 (LPC 16:0) and LPC 18:0 as model analytes. Further, LDI-MS based on the HB/HL-patterned TiO2 NTA matrix is applied to the medical diagnosis of sepsis by analyzing LPC 16:0 and LPC 18:0 with the sera from sepsis-negative and -positive groups. These results reveal that the HB/HL-patterned TiO2 NTA can be a remarkable platform for quantitative analysis. Furthermore, LDI-MS based on the HB/HL-patterned TiO2 NTA matrix has the potential to be a practical approach for sepsis diagnosis.
Keywords: IONIZATION; MATRIX; DESORPTION; SEPSIS; PHOTOCATALYSTS; NANOPARTICLES; ANALYTES; SILICA; CHIP